Performance of HPV E4 and p16INK4a biomarkers in predicting regression of cervical intraepithelial neoplasia grade 2 (CIN2): protocol for a historical cohort study - David Jenkins; Mark H Stoler; Anne Hammer; Torben Steiniche; Lone Kjeld Petersen; Patti E Gravitt; Rikke Kamp Damgaard; Maurits NC de Koning; Wim GV Quint; John Doorbar; Johnny Kahlert (BMJ Open)
Introduction Cervical intraepithelial neoplasia grade 2 (CIN2) represents a spectrum of lesions with variable progression and regression. Pathological diagnosis of CIN2 is subjective and poorly reproducible. Accurate diagnosis and identification of different patterns of CIN2 related to outcome are essential to reduce the risks of overtreatment or undertreatment. It is important to explore novel methods for risk stratification of CIN2 to enable targeted treatment of women at high risk of progression or persistent disease and follow-up of women at low risk. The combination of the novel biomarker human papillomavirus (HPV) E4 with p16INK4a targets steps in the transition from a productive oncogenic HPV infection (CIN1) to a transformed lesion (CIN3) within CIN2. Previous cross-sectional studies suggest that HPV E4 combined with p16INK4a may be valuable for risk assessment of CIN2. However, data on HPV E4/p16INK4a as a predictor for CIN2 regression is lacking.Methods and analysis We will conduct a historical cohort study including 500 women aged 23–40 years with a first CIN2 diagnosis in Aarhus, Denmark during 2000–2010. Women will be eligible if they have undergone active surveillance and have no previous record of hysterectomy, cone biopsy, and CIN2 or worse. Women will be randomly selected through the Danish Pathology Databank. Tissue samples from women included will be sectioned for p16INK4a and HPV E4 immunohistochemical staining in addition to conventional hematoxylin and eosin (H&E) staining. A positive result will be defined as HPV E4 positive. Through the Danish Pathology Databank, we will collect results on all subsequent cervical biopsies. Regression will be used as the primary outcome.Ethics and dissemination The study has been approved by the Ethical Committee in Central Denmark Region (1-10-72-60-20) and registered at the Faculty of Health, Aarhus University. Results will be published in a peer-reviewed journal and presented at scientific meetings.Trial registration number NCT05049252.